Moral Development Strategies for Students at TPQ Anwarul Masalik Keruak - Moh. Irwan Hadi (PALAPA, 2022)
Moral development in non-formal Islamic education is essential for strengthening students’ Qur’anic literacy, manners, worship discipline, and moral-spiritual awareness. This study aims to analyze moral development strategies for students at Taman Pendidikan Al-Qur’an (TPQ) Anwarul Masalik Keruak. This study employed a descriptive qualitative approach. Data were collected through in-depth interviews, observation, and documentation involving the head of the TPQ and three ustaz/ustazah who were actively engaged in Qur’anic learning from August to September 2022. Data were analyzed through data reduction, data display, and conclusion drawing, while trustworthiness was strengthened through source, technique, and time triangulation. The findings show that moral development was implemented through three main strategies: habituating noble character (akhlak al-karimah) toward puberty, training discipline and devotion in worship, and cultivating muraqabah awareness. These strategies were carried out through greeting routines, polite speech, cleanliness practices, Qur’anic recitation, daily prayers, moral advice, exemplary stories, and reinforcement of the belief that every action is under Allah’s supervision. The main constraints included the influence of the environment outside the TPQ, differences in students’ backgrounds, and the absence of a measurable moral development guide. This study concludes that moral development in TPQ needs to be managed consistently, collaboratively, and evaluatively so that moral-spiritual values are not limited to verbal advice but become embedded in students’ daily habits. Theoretically, this study contributes to the literature on moral education in non-formal Islamic learning institutions, while practically, it offers implications for strengthening structured, measurable, and habituation-based moral development programs in TPQ.